2001
DOI: 10.1021/jf010172v
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging Properties of Conjugated Linoleic Acids

Abstract: Conjugated linoleic acids (CLA) were investigated for free radical scavenging properties against the stable 2,2-diphenyl-1-picryhydrazyl radical (DPPH.) by electron spin resonance (ESR) spectrometry and spectrophotometric methods. ESR results demonstrated that CLA directly reacted and quenched free DPPH radicals in benzene, while spectrophotometric analysis showed the radical scavenging capacity of CLA in ethanol. Dose and time effects of CLA-DPPH. reactions were observed in both tests. The ED(50) of CLA was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
136
0
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(153 citation statements)
references
References 18 publications
10
136
0
7
Order By: Relevance
“…This method is easy and applies to measure the overall antioxidant capacity (Prakash 2001) and the free radical scavenging activity of fruit and vegetable juices (Sendra et al 2006). This assay has been successfully utilized for investigating antioxidant properties of wheat grain and bran, vegetables, conjugated linoleic acids, herbs, edible seed oils, and flours in several different solvent systems including ethanol, aqueous acetone, methanol, aqueous alcohol and benzene (Yu 2001;Parry et al 2005). It is a convenient method for the antioxidant assay of cysteine, glutathione, ascorbic acid, tocopherol and polyhydroxy aromatic compounds (Masahiro et al 2005), for olive oil, fruits, juices and wines (Sanchez-Moreno 2002).…”
Section: Dpph Assaymentioning
confidence: 99%
“…This method is easy and applies to measure the overall antioxidant capacity (Prakash 2001) and the free radical scavenging activity of fruit and vegetable juices (Sendra et al 2006). This assay has been successfully utilized for investigating antioxidant properties of wheat grain and bran, vegetables, conjugated linoleic acids, herbs, edible seed oils, and flours in several different solvent systems including ethanol, aqueous acetone, methanol, aqueous alcohol and benzene (Yu 2001;Parry et al 2005). It is a convenient method for the antioxidant assay of cysteine, glutathione, ascorbic acid, tocopherol and polyhydroxy aromatic compounds (Masahiro et al 2005), for olive oil, fruits, juices and wines (Sanchez-Moreno 2002).…”
Section: Dpph Assaymentioning
confidence: 99%
“…Dietary CLA reduced the proportion of macrophages in the mouse mesenteric lymph, inhibited the expression of colonic TNFα, and prevented the colon cancer development induced by inflammation (Evans et al 2010). Moreover, some studies have revealed the antioxidant properties of CLA (van Den Berg et al 1995;Yu 2001). For instance, in rat and chicken, CLA could alleviate doi: 10.17221/8850-CJAS oxidative damages induced by inflammatory agents such as the lipopolysaccharide, gliadin, and sodium arsenite (Zhang et al 2008;Bergamo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is a commercial oxidising radical, which can be reduced by antioxidants. The stable DPPH can be used to study the reaction kinetics of antioxidants, as well as to quantify and compare the free radical scavenging capacities of different antioxidants (Yu, 2001). Fig.…”
Section: Resultsmentioning
confidence: 99%